Perbandingan Tingkat Kedisiplinan Siswa terhadap Tata Tertib Sekolah dalam Meningkatkan Mutu Di SMAN 1 Muaro Jambi dan SMAN 1 Kota Jambi - Afrila, Dinda Suci; Fitria, Nurul; Amalia, Dian; Imrayani, Nagita Pebi; Safitri, Desi (Jurnal Ilmiah Dikdaya, 2023)
This study reveals how the implementation of the code of conduct and discipline of the students in the State High School 1 Muaro Jambi and SMA 1 Negri Jambi City. It is useful to know the implementation of the rules and it is useful to know the difference in student discipline in SMA 1 Negri Muaro Jambi and SMA 1 Negri Jambi City. As we all know, every school has its own rules that must be obeyed by its students. School rules are one of the rules that must be obeyed by students or students and implemented by students, as an embodiment of life that is aware of laws and rules. School rules are signs of life for students in carrying out life in the school community. Coaching teachers in schools is an integral part of efforts to foster awareness of laws and regulations made by the government. Guidance on school rules and regulations is one form of teacher activity in fostering students to get used to obeying the rules. The problem faced in the development of education is how to improve the quality of education, both in terms of knowledge and attitudes, one of the efforts made by the school in fostering student attitudes through school rules and regulations. As we hope at this time there are no students involved in juvenile delinquency, promiscuity, drug use, brawls, and bad ethics even in life, therefore through the development of school rules they are accustomed to carrying out activities in accordance with the applicable rules in the school. community environment. Based on the background the author is interested in studying the comparison of the level of student discipline and school discipline in improving the quality of education, especially in SMA 1 Muaro Jambi and SMA 1 Kota Jambi.